Faktor-Faktor yang Memengaruhi Burnout Syndrome pada Tenaga Kesehatan di Rumah Sakit: A Systematic Review - Sarah Maulida Rahmah; Grace Solely Houghty (Jurnal Ners, 2026)
Burnout syndrome is a serious occupational health problem among hospital healthcare workers and affects the quality of healthcare services. This study aimed to identify and analyze factors influencing burnout syndrome among healthcare workers in hospitals through a systematic review. The research method followed the PRISMA 2020 guidelines with literature searches on PubMed, Scopus, and ProQuest databases. Of the 755 articles identified, 12 articles met the inclusion criteria and were analyzed. Results showed burnout prevalence ranging from 15.1% to 62%, with emotional exhaustion as the dominant component. Factors influencing burnout were categorized into five groups: (1) workload and shift work, with high workload and night shifts increasing burnout risk; (2) social support and good interpersonal relationships functioning as protective factors; (3) job satisfaction and adequate rewards reducing burnout risk; (4) demographic and personal factors such as age, gender, education, and lifestyle; (5) organizational factors including value conflicts, workplace violence, and resource constraints. Comprehensive multi-level interventions encompassing individual, interpersonal, and organizational strategies are needed to prevent and address burnout among healthcare workers in hospitals.Keywords: burnout syndrome, healthcare workers, hospital, risk factors